Statistical implications of inflation targeting : getting the right numbers and getting the numbers right - Carson, Carol S.; Enoch, Charles; Dziobek, Claudia Helene; International Monetary Fund. (Washington, D.C. : Statistics Department, International Monetary Fund, 2002)
This book brings together the experience of central banks and national statistical agencies in countries that focus their monetary policy on inflation targets. Inflation targeting has led to a close interface between these two sets of institutions. When the performance of a central bank is measured in terms of specified price indices, which are usually compiled and disseminated by the national statistical agency, the role of national statistical agencies becomes central to the credibility of monetary policy. Data needs and uses have also shifted, with implications for national and international statistics compilation: market data have gained in importance; less emphasis is placed on traditional monetary aggregates; and greater attention is paid to timeliness, adherence to sound economic accounting standards, and other aspects of data quality.
"Papers presented at the IMF Seminar on Statistical Implications of Inflation Targeting, Washington, D.C., February 28-March 1, 2002."
Includes bibliographical references (p. 360-374).
nmn, 24/11/18
Loans
Keywords: Inflation targeting; International monetary fund